How US dental schools can better prepare their students to perform operative procedures. Issue 4 (16th November 2020) - He, Karen; Breitman, Leela; Lee, Jennifer; Van Doren, Emily; Li, Alice; Donoff, R. Bruce
Abstract: Objective: The aim of this study was to characterize the curricular and supplemental resources used by dental students during their operative dentistry course, survey students' perception of each resource's "helpfulness, " and assess students' perceptions of preparedness to perform operative dental procedures in clinical settings. Methods: American Student Dental Association delegates at all accredited dental education programs in the United States were asked to forward an email to students enrolled at their respective institutions explaining the purpose of the study and asking them to fill out our survey. The response rate was calculated using the targeted enrollment data found in American Dental Education Association Official Guide to Dental Schools. Results: A total of 715 qualified respondents completed our questionnaire for a response rate of 13.5%. 90% of students felt at least "moderately prepared" to perform operative procedures in the clinical environment. The 3 most common curricular resources provided to students were lecture slides (n = 707, 99%), live lectures (n = 664, 93%), and live faculty demonstrations (n = 547, 77%). YouTube was the most common supplemental resource utilized by students (n = 575, 80%). When asked to select which resources were the most helpful for their learning, 49% (270/547) selected live faculty demonstrations, 27% (153/575) selected YouTube videos, and 23% (155/664) selected lectures/lecture slides. Conclusion: To best meet the expectations of the current generation of dental students and to prevent early‐stage dental learners from being influenced by clinical misinformation online, dental schools should consider adapting and producing more online, video‐based learning resources for their curricula.